Light weight concrete panel wall / Badrul Hisham Mohd Zamri - Mohd Zamri, Badrul Hisham (Universiti Teknologi MARA, Perak, 2019)
Nowadays, the construction of the building can be said to be very rapid. All the construction emphasizes the time aspect of getting a project done in a timely manner. Therefore, the IBS method is used to save construction time. Therefore, this report discusses the IBS system for housing projects. The objective of this report is to know how to install the IBS panel and the problems it encounters and the solution. It will focus on installation of lightweight concrete panels that give good housekeeping at site. The observations, interview session and document reviews are used for references and to gain more knowledge. According to the project housing that started in 1960 by government using IBS, IBS system is not new things in Malaysia but this system not more emphasis, but the government already set in 2020, all government projects especially will involve in JBS system. So that, all contractors should be involved in IBS projects before 2020.